2006
DOI: 10.1007/s11325-006-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of obstructive sleep apnea in patients presenting to a tertiary care center

Abstract: The objective of this prospective observational clinical study is to derive and validate a diagnostic model for prediction of obstructive sleep apnea (OSA) in subjects presenting with non-sleep-related complaints in a tertiary care center in north India. We included 102 subjects (group I, range 31-70 years) presenting to the hospital with non-sleep-related complaints. None of the subjects had any significant comorbid illness such as respiratory or congestive cardiac failure. All subjects underwent detailed eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
6
18
1
1
Order By: Relevance
“…clinical prediction Models: Four studies evaluated the performance of clinical prediction models against PSG, 61,[76][77][78] and three studies 75,79,80 evaluated these models against HSAT. Two of the studies compared respiratory parameters against PSG: a study involving a Chinese cohort that evaluated snoring while sitting 76 and another single study assessing respiratory conductance and oximetry.…”
Section: Multivariable Apnea Prediction Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…clinical prediction Models: Four studies evaluated the performance of clinical prediction models against PSG, 61,[76][77][78] and three studies 75,79,80 evaluated these models against HSAT. Two of the studies compared respiratory parameters against PSG: a study involving a Chinese cohort that evaluated snoring while sitting 76 and another single study assessing respiratory conductance and oximetry.…”
Section: Multivariable Apnea Prediction Questionnairementioning
confidence: 99%
“…Other studies compared clinical prediction rules including age, waist circumference, ESS score and minimum oxygen saturation, and another evaluated gender, nocturnal choking, snoring and body mass index against PSG; these reported reasonably high sensitivity (range of 0.72-0.94) and specificity (range of 0.75-0.91) considering different AHI thresholds. 61,77 Clinical prediction rules have been evaluated against HSAT in select populations, i.e., the elderly, 75 bariatric surgery candidates, 79 and commercial drivers. 80 These studies reported sensitivities ranging from 0.76-0.97 and specificities ranging from 0.19-0.75 using an AHI cutoff of ≥ 30 75,79,80 (see supplemental material, Table S29 through Table S31).…”
Section: Multivariable Apnea Prediction Questionnairementioning
confidence: 99%
“…There has been only one previous Indian study in which a diagnostic model was derived and validated for the prediction of OSA in subjects presenting with non-sleep-related complaints [11]. The results of our study indicate that the relatively easier morphometric measurements afforded by the SMM enable faster screening for OSA in a primary health care setting.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies for prediction of OSA have used a wide variety of statistical approaches, photographic analysis and clinical and photographic measurements to predict the presence of OSA (19)(20)(21)(22). These approaches have been limited by poor sensitivity, specifi city, lack of prospective validation and taking too much time for computations and analysis.…”
Section: Discussionmentioning
confidence: 99%